2020
DOI: 10.1016/j.jaad.2019.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Topical cholesterol/lovastatin for the treatment of porokeratosis: A pathogenesis-directed therapy

Abstract: Background: Porokeratosis is associated with mevalonate pathway gene mutations. Therapeutic options are few and often limited in efficacy.Objective: On the basis of preventing the accumulation of toxic metabolites while replenishing essential end-products, we studied the efficacy of topical lovastatin/cholesterol in different variants of porokeratosis.Methods: A series of 5 patients with disseminated superficial actinic porokeratosis (DSAP,n=1), porokeratosis palmaris et plantaris disseminata (PPPD,n=2) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 34 publications
4
115
1
15
Order By: Relevance
“…Cross-sectional data of patients with hidradenitis suppurativa, morphea, pemphigus and psoriasis from five earlier cross-sectional surveys were re-analysed. [6][7][8][9][10] The original DLQI bands by Hongbo et al 5 were selected as anchor items for mapping DLQI-R scores. Six separate sets of DLQI-R score bands were produced: (A) cut-off scores derived from a receiver operating characteristic (ROC) analysis; (B) cut-off scores from the ROC…”
mentioning
confidence: 99%
“…Cross-sectional data of patients with hidradenitis suppurativa, morphea, pemphigus and psoriasis from five earlier cross-sectional surveys were re-analysed. [6][7][8][9][10] The original DLQI bands by Hongbo et al 5 were selected as anchor items for mapping DLQI-R scores. Six separate sets of DLQI-R score bands were produced: (A) cut-off scores derived from a receiver operating characteristic (ROC) analysis; (B) cut-off scores from the ROC…”
mentioning
confidence: 99%
“…However, mounting evidence suggests that many patients with porokeratosis may harbor postzygotic mosaic somatic mutations in enzymes of the mevalonate biosynthetic pathway . If this is true, treatment with inhibitors of HMG‐CoA reductase or other preceding steps in the mevalonate biosynthetic pathway may represent a future therapeutic approach …”
Section: Discussionmentioning
confidence: 99%
“…All the patients showed tolerance to the therapy with no reported irritation, redness or allergic contact dermatitis at the treatment sites. The results showed that topical cholesterol/lovastatin is effective in treating porokeratosis [ 131 ].…”
Section: Cholesterol-based Compounds For the Treatment Of Dermatolmentioning
confidence: 99%